Bilateral deficit in vertical jumping in pre-pubertal boys and girls - Veligekas, P.; Bogdanis, G.C. (Journal of Physical Education and Sport, 2013)
The purpose of the study was to compare bilateral deficit in jumping (i.e. when the sum of left and right leg jump height is greater than the two-leg jump) between pre-pubertal boys and girls. One hundred and seventy two children (83 boys and 89 girls between) were divided into two groups (10 and 12 years old) and performed oneleg and two-leg counter movement jumps without arm swing on a contact mat. The bilateral jump deficit index was calculated as: 1-(right+left leg jump height)/two-leg jump height x 100. Peak leg power output during jumping was also calculated and was scaled with body mass. Jump height and relative leg peak power were similar in boys and girls of both age groups. However, the bilateral jump deficit index was always greater and positive in boys compared with girls, indicating that the two-legged jump performance was better than the sum of right and left leg jumps. This difference between boys and girls remained even when training history was taken into account (trained vs. untrained children), indicating that it is independent of training status. Also, when differences in bilateral deficit were examined with analysis of covariance, with maturity offset (an index of biological maturation) as the covariate, boys still had greater values than girls (12.9±2.0 vs. -1.6±2.3%, p<0.01). In conclusion, the results of the present study indicated that the there was no bilateral deficit for vertical jumping for boys at this age range. In contrast, girls had a bilateral index that was close to zero, indicating equal two-leg and sum of two legs jumps. These differences between boys and girls may be explained by a reduced ability to activate motor units during pre-puberty and/or superior motor skill ability (i.e. balance on one leg and jump) of girls over boys at that age. © JPES.